(untitled) (Journal of Hama University, 2022)
The aim of the research is to identify the various factors affecting the consumption of sheep milk in the Salamiyah area, where data were collected from a random sample of consumers of sheep milk and its derivatives from the Salamiyah area and some of its surrounding villages, the size of which was 100 respondents for the year 2021, and it also aimed to determine the relationship between sheep milk consumption and the economic and social characteristics of consumers, and the results of estimating the consumption function showed that two variables namely the price of a kilogram of yogurt and the price of a kilogram of cheese. they explained (64%) of the change in monthly milk consumption. The average family consumption of sheep’s milk was estimated at 18.5 kg per month, with the largest consumption reaching between 7 and 16 kg per month.